1972
DOI: 10.1063/1.2946413
|View full text |Cite
|
Sign up to set email alerts
|

The Argonne Cancer Research Hospital Cyclotron

Abstract: The installation of a cyclotron (Cyclotron Corp. CS-15) in an existing building without disruption of other operations was accomplished with relatively little difficulty using overdesigned i shielding. (6 feet of ordinary concrete). Back-' * Operated by the University of Chicago for the United States .. Atomic Energy Commission. DISTRI BUTION OF THIS DOCUM iNT IS UNLIM ITED 4-DISCLAIMER This report was prepared as an account of work sponsored by an agency of the United States Government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This is analogous to the use of radiolabeled microspheres 9 to 15 micrometers in diameter; however, except for lung imaging, injection of degradable microspheres is not feasible. The agents that are most commonly used and have good extraction in the heart and kidneys are "3NH3 (35) and 82Rb (36). Agents for brain studies have been developed for single-photon tomography (9), but are still under development for positron tomography.…”
Section: Kinetic Analysis In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…This is analogous to the use of radiolabeled microspheres 9 to 15 micrometers in diameter; however, except for lung imaging, injection of degradable microspheres is not feasible. The agents that are most commonly used and have good extraction in the heart and kidneys are "3NH3 (35) and 82Rb (36). Agents for brain studies have been developed for single-photon tomography (9), but are still under development for positron tomography.…”
Section: Kinetic Analysis In Vivomentioning
confidence: 99%
“…Perfusion measurements have been made with 13NH3 (35) or 82Rb (36), and metabolism measurements with FDG and "C-labeled palmitic acid. Palmitic acid has been used to evaluate the presence of infarcts as well as regional rates of beta-oxidation (50), and FDG has been used to investigate glycolytic rates (51).…”
Section: Medical Science Applicationsmentioning
confidence: 99%
“…For example, the rapidity of ammonia clearance from the systemic circulation does not appear to have been fully appreciated. Workers who have administered [ 13N]ammonia by intravenous injection in several species, including humans, have found that the bulk of the tracer is removed from blood within 1-2 min of injection (41,42,48,49,174,185). In rats sacrificed by cardiac excision 12 seconds after intravenous [13N]ammonia injection, < 6% of the dose was recovered in pooled chest blood representing about half the blood volume (186).…”
Section: [L3n]amrnonia Physiology and Metabolism In Mammalsmentioning
confidence: 99%
“…Intravenous [ 13N]-ammonia yields significant accumulations of 13N in the liver of all species studied. Furthermore, in all cases in which liver 13N has been studied as a function of time, a steady rise to a peak concentration between 10 and 20 min after injection has been observed (rats (186), dogs (217), humans (41,48)). Following intravenous [13N]ammonia, accumulation of label in mouse liver was reported to be 8.0 and 5.9 % dose/g at 10 and 30 min, respectively (219) (or about 10 and 7 % dose, respectively).…”
Section: Brain Ammonia Extraction: Mechanism Of Entrymentioning
confidence: 99%
“…The use of radiolabeled enzyme inhibitors as potential organ-imaging agents has been suggested by several investigators. Wieland et al (1) studied the distribution of several radiolabeled inhibitors of the adrenal cortex enzymes, 20a-hydroxylase, 1 ID-hydroxylase, and 17a-hydroxylase. The finding that some of these inhibitors localized in the adrenal cortex suggested that radiolabeled enzyme inhibitors might be useful in the design of new diagnostic radiopharmaceuticals.…”
mentioning
confidence: 99%